Bone asymmetries in the limbs of children tennis players: testing the combined effects of age, sex, training time, and maturity status - Palaiothodorou, D.; Antoniou, T.; Vagenas, G. (Journal of Sports Sciences, 2020)
This study estimated upper and lower limb bone mineral content (BMC) and bone area (BA) in 48 children tennis players (24 boys, 24 girls) aged 7-13 years. The sample comprised four age groups (8.2 ± 0.44, 9.5 ± 0.13, 10.5 ± 0.33, 12.2 ± 0.58). BMC and BA were measured via DXA, and sexual maturity by the Tanner scale, then used as a binary: prepubertal vs peripubertal. Total training time (TTT) included all playing years. Arms were asymmetric and legs symmetric. Boys were more asymmetric than girls in BMC (18% vs 13%) and BA (11% vs 8%). Pre-pubertal children were less asymmetric than peri-pubertal in BMC (14% vs 18%) and in BA (9.4% vs 10%). Bone growth changed with age and TTT markedly better in the dominant arm. The linear combination of TTT, sex, and maturity binary extracted 59% of BMC asymmetry and only 21% of BA asymmetry. For both bone parameters the sex effect was significant only for the pre-pubertal children. Training time constitutes the best predictor of bone asymmetry compared to age, sex, and maturity; when adequate, playing arm bone hypertrophy may be detectable at the age of 7-8 years. These results have health and performance implications.Knochenasymmetrien in den Gliedmaßen von Tennisspielern im Kindesalter: Prüfung der kombinierten Effekte von Alter, Geschlecht, Trainingszeit und Reifestatus